People's Sovereignty in the System Presidential Threshold in the Perspective Siyasah Al-Syar’iyyah - Iqbal Katrino; Yus Afrida (Institut Agama Islam Negeri Palangka Raya, 2021)
UU no. 7/2017 concerning General Elections, is the legal protection for the implementation of the 2019 General Election using the system presidential threshold. The problem is, this is seen as castration of individual rights where power is in the hands of the people. Equal treatment before the law and politics in the context of nominating the President and Vice President is limited to parties that are part of and meet the threshold in the 2014 general election. This research found that the implementation of the system Presidential Threshold in Indonesia was an embodiment of the people's sovereignty itself. Where the individual directly determines the leader, and in making the requirements to become a leader, and the DPR is a representation of the people. This eliminates concerns in the community when the system will be ratified Presidential Threshold in Law Number 7 of 2017 concerning Elections so that the people's sovereignty in the threshold system is by siyasah syar’iyyah where ahlul halli wa al-‘aqdi can determine candidate leaders and Bai’ah is a form of the general election in determining the leader.